Digitizing Website-Based Qur'anic Tafseer - Fitriani Fitriani; Izzah Faizah Siti Rusydati Khaerani (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the website-based interpretation of the al-Qur’an in the digital era. This qualitative research method is through literature study which attempts to reexamine the area of ​​tafsir studies, by taking the object of the phenomenon of the al-Qur’an interpretation practically in the digital world, while the approach to data interpretation uses content analysis. This research discusses the notion of digitization, al-Qur’an, and tafsir, the dynamics of interpretation in the digital era, and website-based interpretations of the al-Qur’an. This research concludes that the website-based interpretation of the al-Qur’an makes it easy to study and understand the contents of the al-Qur’an. As well as being able to adapt and meet the needs of today’s modern society. The Interpretation of the website-based al-Qur’an, among them TafsirQ.com, Tafsirweb.com, and Qur’an Kemenag.